Workplace incivility as modern sexual prejudice - Di Marco, D.; Hoel, H.; Arenas, A.; Munduate, L. (Journal of Interpersonal Violence, 2018)
Although discrimination on grounds of sexual orientation is prohibited by law in many countries, negative prejudices against Lesbian and Gay (LG) people, as a stigmatized minority, might be internalized by co-workers, being a source of a modern and subtle form of discrimination. Results from 39 in-depth semi-structured interviews with LG employees show that they are victims of workplace incivility which is manifested through jokes, use of language, stereotypes, and intrusive behaviors. Such acts are barely recognizable as a form of discrimination, due to the absence of any reference to sexual orientation, and for this reason it is more difficult to act against them at an organizational level. This is the first study that demonstrates how workplace incivility toward LG employees can be an expression of a subtle form of discrimination. It shows that discrimination on grounds of sexual orientation has not disappeared; it has simply changed its manifestations. Contributions and implications of the study are discussed from a theoretical and a practical perspective.